1995
DOI: 10.1007/bf01539133
|View full text |Cite
|
Sign up to set email alerts
|

The increased potential for the production of inflammatory cytokines by Kupffer cells and splenic macrophages eight days after thermal injury

Abstract: Burn patients often experience a devastating inflammatory response to infection within the first two weeks after thermal injury. The inflammatory cytokines IL-6, TNF and IL-1 have been implicated in this condition but most studies have focused on the abnormal levels of cytokines in the plasma. In this study the production of cytokines was compared for Kupffer cells versus splenic macrophages; endotoxin (LPS) stimulation versus no stimulation; and burn (post burn days 1, 3 and 8) versus no burn (control). Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…This is consistent with the report of Wu et al that the plasma levels of TNF-α were undetectable in rats on day 8 following burn injury. 19 However, the plasma TNF-α concentrations were higher than the detection limit of the kit in 75% of the TPN-fed animals. Previous animal studies have shown that the plasma TNF-α concentration is significantly increased in rats infused with TPN than that in rats fed with TEN after endotoxin injection and bacterial intraperitoneal challenge.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the report of Wu et al that the plasma levels of TNF-α were undetectable in rats on day 8 following burn injury. 19 However, the plasma TNF-α concentrations were higher than the detection limit of the kit in 75% of the TPN-fed animals. Previous animal studies have shown that the plasma TNF-α concentration is significantly increased in rats infused with TPN than that in rats fed with TEN after endotoxin injection and bacterial intraperitoneal challenge.…”
Section: Discussionmentioning
confidence: 98%
“…As [18,22,30,31]. Thus, we were interested in determining if changes in TLR4 responses could contribute to the development of severe SIRS and MOF in a mouse injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Acting via cytokine-receptor interactions, intracellular signaling pathways, and ultimately influencing transcription factors, these cytokines are able to modulate the promoter regions of multiple acute phase proteins. [5][6][7] Although the effects that individual and small combinations of cytokines have on acute phase protein production have been well described, the temporal sequence by which this occurs after burn injury has been poorly examined. Kataranovski 4 found a correlation between an increase in alpha 2 -microglobin and haptoglobin 12 hours after injury, a concominant increase in serum IL-6 activity at 6 and 12 hours after injury, and an increase in TNF-␣ activity at 12 hours after injury.…”
mentioning
confidence: 99%